How Artificial Intelligence Helps Students to Learn English in Depth - Seyedi, Akam; Yeganeh, Mohammad Ali Alaei; Noorzad, Diar; Firouzi, Shahrooz; Qurbani, Mahsa; Shakeri, Erfan; Osati, Kiana (Advances in Social Sciences Research Journal, 2024)
This research examines the applications and advancements of artificial intelligence (AI), a computer-based simulation of human intelligence meant to act like humans. AI is one of the driving forces behind the 4.0 industrial revolution, making teaching and learning more accessible in schools. This study aims to understand the function of AI in ELT and examine AI technologies in ELT. This is a library research project. The findings indicate that AI provides a positive learning environment for learning English. Depending on the learner’s current level of English, career needs, or hobbies, it has much potential to create a customized environment where students can simultaneously use their senses to learn English. AI boosts practical abilities like writing and offers a trustworthy simulation dialogue platform like spoken English. It maximizes the teaching impact of English in ELT while increasing students’ practice ability. With the advancement of technology and platforms, learning English has gotten simpler. Artificial intelligence technology provides the chance to enhance English linguistic competence.[1]